Hemostatic Status of Neonates with Perinatal Hypoxia, Studied via NATEM in Cord Blood Samples - Marina Tsaousi; Rozeta Sokou; Abraham Pouliakis; Marianna Politou; Nicoletta Iacovidou; Theodora Boutsikou; Alma Sulaj; Eleni Karapati; Andreas G. Tsantes; Argirios E. Tsantes; Serena Valsami; Zoi Iliodromiti (MDPI AG, 2024)
Background: Perinatal hypoxia may result in coagulation dysfunction. Diminished blood flow or oxygen to the fetus/neonate during the perinatal period can cause bone marrow and liver function impairment, leading to thrombocytopenia, impaired synthesis of clotting and fibrinolytic factors, and increased destruction of platelets in the small blood vessels. The goal of the present study was to evaluate the hemostatic status of newborns with perinatal hypoxia via the non-activated thromboelastometry (NATEM) assay in cord blood samples. Methods: 134 hypoxic neonates born in our maternity unit over a 1.5-year period were enrolled in this observational cohort study, and 189 healthy neonates served as the control group. Participation in the study was voluntary and parents signed informed consent prior to recruitment. Demographic and clinical data were recorded on admission, and the NATEM method was performed on cord blood samples. The following NATEM values were evaluated: clotting time (CT), alpha angle (α-angle), clot formation time (CFT), clot amplitude at 5 and 10 min. (A5, A10), maximum clot firmness (MCF), clot lysis index at 60 min. after CT (LI60), and maximum clot elasticity (MCE). Statistical analysis was conducted utilizing the SAS for Windows 9.4 software platform. Results: Neonates with perinatal hypoxia exhibited decreased fibrinolytic potential in comparison to healthy neonates, as indicated by increased LI60, and this difference was statistically significant (LΙ60: 94 (92-96) Vs 93 (91-95), p value = 0.0001). There were no statistically significant differences noted among the remaining NATEM variables. Conclusion: Our findings indicate decreased fibrinolytic potential in hypoxic neonates in comparison to healthy neonates, suggesting that NATEM could serve as an effective tool for promptly identifying hemostasis dysfunction in this group of neonates.